Livonian and Courlander nobility in Samogitia in the 17th and 18th century - Rachuba, Andrzej (Klio - Czasopismo Poświęcone Dziejom Polski i Powszechnym, 2020)
The main issue of this paper is Livonian nobles’ immigration to Lithuania. This topic is very difficult to investigate, because of significant deficiency in sources presenting a registration of estates and real estate transactions from Livonia and Courland. There are no registers of owners, tenants, or pledgees of estates from Grand Duchy of Lithuania from the 16th to the 18th century and therefore primary sources for research presented in the paper are military and tax registers from 1567, 1621, 1667, 1690 and 1765. Unfortunately those registers have many disadvantages, which need to be highlighted. The author of the article analysed transformations of nobles’ surnames. The findings of this analysis show that in the above mentioned period of time several dozens of Livonian and Coulrand noble families settled in Samogitia. Those families were forced to leave Livonia as they remained loyal to the Polish king, although they also wanted to improve their economic status. The paper was originally published as Inflantczycy i Kurlandczycy na Żmudzi w XVI–XVIII wieku, “Klio” 2015, vol. 35 (4), pp. 45–68; DOI: 10.12775/KLIO.2015.044.